Efficient removal of total arsenic (As3+/5+) from contaminated water by novel strategies mediated iron and plant extract activated waste flowers of marigold. (February 2023) - Upadhyay, Sudhir K.; Devi, Priyanka; Kumar, Vinay; Pathak, Himanshu K.; Kumar, Prasann; Rajput, Vishnu D.; Dwivedi, Padmanabh
Abstract: In this investigation, marigold flower-waste was activated with iron salts (MG-Fe), subsequently marigold plant extract (MG-Fe-Ex) for the adsorptive elimination of As 3+ and As 5+ from contaminated water. The governing factor such as medium pH, temperature, pollutant concentration, reaction time, adsorbent dose were considered for the study. The complete elimination of As 3+/5+ was recorded with MG-Fe-Ex at pH 8.0, 90 min, 30 °C, dose 4 g/L, 20 mg/L of As 3+/5+ and shaking rate 120 rpm, while under the identical experimental condition, MG-Fe exhibited 98.4% and 73.3% removal for As 5+ and As 3+, respectively. The MG-Fe-Ex contains iron oxides (Fe2 O3 and Fe3 O4 ) as a result of iron ions reaction with plant bioactive molecules as evident from x-ray diffraction analysis (XRD), energy dispersive x-ray spectroscopic (EDS) and Fourier transform infrared (FTIR) spectroscopic study. The adsorption data of As 3+/5+ on MG-Fe and MG-Fe-Ex was best fitted by pseudo-first order kinetic and freundlich isotherm except As 5+ adsorption on MG-Fe-Ex that can be described by langmuir isotherm model. The prevailing mechanism in adsorption of As 3+/5+ on both adsorbent might be hydrogen bonding, electrostatic attraction and complexation. From the above, it is confirmed that MG-Fe-Ex adsorbent has high potential and can be used for the adsorptive elimination of As 3+/5+ from contaminated water in sustainable and environmentally friendly way. Graphical abstract: Image 1 Highlights: Synthesized novel activated adsorbents MG-Fe and MG-Fe-Ex from Marigold flower waste. Greener approach is applied in fabrication of MG-Fe and MG-Fe-Ex. MG-Fe-Ex exhibited complete removal of both As 3+ and As 5+ with the optimized experimental conditions but MG-Fe can't. MG-Fe-Ex associated with bioactive molecules resultant into higher adsorption of As 3+/5+ . MG-Fe-Ex exhibited complexation, H-bonding and electrostatic attraction in As adsorption.